Toll-Interacting Protein in Resolving and Non-Resolving Inflammation - Kowalski, Elizabeth J. A.; Li, Liwu (Frontiers in Immunology, 2017)
Innate leukocytes manifest dynamic and distinct inflammatory responses upon challenges with rising dosages of pathogen associated molecular pattern molecules (PAMPs) such as lipopolysaccharide (LPS). To differentiate signal strengths, innate leukocytes may utilize distinct intra-cellular signaling circuitries modulated by adaptor molecules. Toll-interacting protein (Tollip) is one of the critical adaptor molecules potentially playing key roles in modulating the dynamic adaptation of innate leukocytes to varying dosages of external stimulants. While Tollip may serve as a negative regulator of NFκB signaling pathway in cells challenged with higher dosages of LPS, it acts as a positive regulator for low-grade chronic inflammation in leukocytes programmed by subclinical low-dosages of LPS. This review aims to discuss recent progress in our understanding of complex innate leukocyte dynamics and its relevance in the pathogenesis of resolving versus non-resolving chronic inflammatory diseases.